2009
DOI: 10.1007/s00246-008-9374-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum Level of Soluble Intercellular Adhesion Molecule-1 Correlates with Pulmonary Arterial Pressure in Children with Congenital Heart Disease

Abstract: Children with CHD and pulmonary hypertension had a trend toward elevated sICAM-1 compared with CHD children who had no pulmonary hypertension. A linear correlation was found between mean pulmonary arterial pressure and sICAM-1 level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Recently, Bakouboula et al (2) found that there was a positive correlation between endothelial stimulation, mean PAP, and sVCAM-1 in adult patients. Another study of children with congenital heart diseases showed that sICAM-1 levels were significantly higher in PAH group (8). Like these studies, we also found a strong association between mean PAP and preoperative sICAM-1 level.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Recently, Bakouboula et al (2) found that there was a positive correlation between endothelial stimulation, mean PAP, and sVCAM-1 in adult patients. Another study of children with congenital heart diseases showed that sICAM-1 levels were significantly higher in PAH group (8). Like these studies, we also found a strong association between mean PAP and preoperative sICAM-1 level.…”
Section: Discussionsupporting
confidence: 86%
“…Cardiac surgery is also associated with increased plasma adhesion molecule levels (7). Recently; increased sICAM-1 levels have been reported in patients with L-R shunt with PAH (8). Cardiac surgery of the patients with PAH carries increased risk of mortality and morbidity which can be reduced by using prognostic markers of endothelial activation and there is no study to investigate prognostic value of ICAM and VCAM in this group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The ICAM-1 levels were higher in patients with a mean PAP of >25 mmHg, and mean PAP was the strongest independent marker of ICAM-1 levels, according to the multiple regression model. 10 We too found that ICAM-1 level correlated rather strongly with systolic and mean PAP ( Fig. 3 and Table III).…”
mentioning
confidence: 55%
“…5,6 In the medical literature, 7-9 elevated serum concentrations of adhesion molecules have been detected in several diseases, such as diabetes mellitus, coronary heart disease, atherosclerosis, and rheumatoid arthritis. Sungprem and colleagues 10 showed that serum ICAM-1 level was increased in patients with PAH. …”
mentioning
confidence: 98%
“…Burke et al demonstrated increased expression levels of the adhesion molecules ICAM-1 and VCAM-1 in the pulmonary arteries of chronically hypoxic rats (11). Furthermore, elevated levels of these adhesion molecules have been demonstrated in children with congenital heart disease and PH (40), whereas amelioration of chronic hypoxiainduced PH was associated with decreased ICAM-1 expression (41). Although few published reports have demonstrated that CXCR7 directly modulates the expression of these adhesion proteins (20), the involvement of CXCR7 in cell adhesion was shown in several recent studies.…”
Section: Discussionmentioning
confidence: 99%